2009
DOI: 10.1093/brain/awn253
|View full text |Cite
|
Sign up to set email alerts
|

A deficit of brain dystrophin impairs specific amygdala GABAergic transmission and enhances defensive behaviour in mice

Abstract: Duchenne muscular dystrophy (DMD) is accompanied by cognitive deficits and psychiatric symptoms. In the brain, dystrophin, the protein responsible for DMD, is localized to a subset of GABAergic synapses, but its role in brain function has not fully been addressed. Here, we report that defensive behaviour, a response to danger or a threat, is enhanced in dystrophin-deficient mdx mice. Mdx mice consistently showed potent defensive freezing responses to a brief restraint that never induced such responses in wild-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
146
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(161 citation statements)
references
References 62 publications
14
146
1
Order By: Relevance
“…Collectively, these results correspond with findings that highlight the effects of stress exposure-induced amygdala modulation of learning and memory processes (36). More specifically, increased freezing responses have been associated with altered amygdalar activity (37,38); thus the increased freezing exhibited by tKO mice corresponds to the increased stress-potentiated ASR and to the alterations in amygdalar functions described in detail below. The comparable freezing exhibited by both genotypes in the context test may result from an interaction between enhanced amygdalar functions and a stress-induced deficit in hippocampal functions.…”
Section: (G and H) Asr (G)supporting
confidence: 86%
“…Collectively, these results correspond with findings that highlight the effects of stress exposure-induced amygdala modulation of learning and memory processes (36). More specifically, increased freezing responses have been associated with altered amygdalar activity (37,38); thus the increased freezing exhibited by tKO mice corresponds to the increased stress-potentiated ASR and to the alterations in amygdalar functions described in detail below. The comparable freezing exhibited by both genotypes in the context test may result from an interaction between enhanced amygdalar functions and a stress-induced deficit in hippocampal functions.…”
Section: (G and H) Asr (G)supporting
confidence: 86%
“…In the mdx mouse, lack of Dp427 is associated with reduced receptor clustering, impairing specific amygdala GABAergic transmission and enhancing defensive behaviour in response to danger. 32 In contrast, Dp140 localizes in glial cells and Dp71 is expressed in the perivascular astrocytes, which is required for anchoring aquaporin-4. Loss of Dp71 is associated with reduced levels of aquaporin-4, thus altering transmembrane water permeability.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that this form of protein dystrophin colocalizes with inhibitory GABA receptor clusters at the postsynaptic membranes of hippocampal and neocortical pyramidal neurons where the synapse function is modulated. [45][46][47][48] According to various studies this dystrophin isoform has a stabilizing effect on the GABA receptors by limiting their lateral diffusion outside the synapse. 49,50 Importance of GABA receptors for the regulation of cognition, emotion and memory is increasingly being recognized.…”
Section: Discussionmentioning
confidence: 99%